Influence of destination attractiveness on place satisfaction and environmentally responsible behaviour in marine parks - Mohammed, Nadzirah (Penerbit Universiti Malaysia Terengganu, 2020)
Malaysia is well known as one of the 12 mega biodiverse countries in the world. In order to leverage the existing tourism product, the government has made some of the islands in Malaysia as official Marine Parks. The responsibilities of Marine Parks are to protect and manage the marine ecosystem systematically in order to market Malaysia as a nature hub. It is where tourist’s positive environmental behaviour plays an important role in sustaining the destination. However, tourism activities have impacted the nature of the Marine Parks and there are also negative reviews from the tourists regarding the landscape, services and safety in Malaysia’s Marine Park. In relation to this, it is important to understand the tourists’ attitude and behaviour on ecological issues as it can limit the environmental problems. The objective of this study is to examine the relationship between destination attractiveness, place satisfaction and environmentally responsible behaviour of tourists in Marine Parks. A survey had been conducted on selected Marine Parks of Malaysia which are Tioman Island, Payar Island, Redang Island and Perhentian Island. Data was collected from 275 tourists who visited these Marine Parks. This study uses descriptive statistics to identify the information of tourists’ profile and Structural Equation Modelling (SEM) to examine the relationships of the variables. Results show that destination attractiveness affects environmentally responsible behaviour of tourists in the Marine Parks through place satisfaction. It indicates that tourists who are satisfied with the Marine Park attractiveness tend to commit environmentally responsible behaviour. Thus, this will assist in enhancing the destination marketing strategy as well as sustaining the destination through identifying current tourists’ experience in Marine Parks. The paper ends with discussions and suggestions for future empirical research.